Great Safety and Efficacy of a New Drug-eluting-stent manufactured in a developing country at minimal cost: the VSTENT at 3 years follow-up. (3rd October 2022) - Ho, D; Vu, L; Nguyen Van, T; Nguyen, T
Abstract: Background: In the care patients with coronary artery disease, a new drug-eluting stent, the VSTENT, covered with sirolimus was designed and manufactured in a developing country at minimal cost. Beside the clinical concern, from an engineering perspective, the questions were: Was this stent flexible? What was its radial strength? Did this stent brace itself against the wall with a strong strut network? What was the cell size and design? Methods: From 6.2019 to 8.2020, 150 patients from 5 hospitals underwent PCI with a new VSTENT in 212 lesions. At the index PCI (D1), a subgroup of 61 patients (40%) was preselected to undergo additional imaging procedures including intravascular ultrasound (IVUS=41) or optical coherence tomography (OCT=20). All patients were followed-up clinically every month for one year. At 6 months (D180) they underwent digital subtraction angiography (DSA=143) or a second IVUS or OCT for the intravascular subgroup. The rate of invasive imaging follow-up was 95% for DSA, 92% for IVUS and 95% for OCT. The rate of major adverse cardiovascular events (MACE: mortality, in-stent restenosis (ISR), Target lesion revascularization (TLR) and data on radial strength, longitudinal flexibility, expansion and coverage were calculated. Results: In all patients, the technical success was 100% (successful balloon inflation, complete stent expansion, uneventful balloon removal). The VSTENTs were deployed in arteries of all sizes: small with diameter (D) = 2.5mm in 11.3%, D= 2.75mm in 24.1%, and in large arteries D= or >3mm in 66.6% of patients. The stent length varied from 15–38mm with 80% >20mm. 92% had good apposition as evidenced by OCT or IVUS. There was no acute in-stent thrombus, no loss of side branch and no perforation. There was one cardiac arrest with successful resuscitation. The bench and angiographic data on radial strength, longitudinal flexibility, expansion and coverage were excellent In Figure 1, The VSTENT design has open cells in the middle and closed cell at both distal segments. This design of mixed closed and open cell increases the radial strength at both ends while preventing the diametric difference (dog-boning effect) In Figure 2, after deployment of a VSTENT, the size of the open cell design in the middle of the stent is approximately 3.40 mm 2 while the size of the distal closed cells design is 1.7 mm 2 . At 6 months, the rate of angiographic ISR inside the stent and within the 5 mm from the two ends was 3.5%. The rate of late lumen loss was 0.8mm in the in-stent segment and 0.07mm within 5mm of the two ends. The composite MACE was 4.7% with 1 mortality (0.7%) and 4 TLRs. At 36 months follow-up, only one TLR was reported. Conclusions: At 3 years follow-up, the rate of angiographic ISR and TLR of the VSTENT was low. The data on radial strength, longitudinal flexibility, expansion and coverage were excellent. The VSTENT could be an affordable choice for interventional cardiology service in developing countries. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): United Healthcare